Can remote sensing enable a Biomass Climate Adaptation Index for agricultural systems? - Ferguson, Amy; Murray, Catherine; Mesfin Tessema, Yared; McKeown, Peter C.; Reymondin, Louis; Loboguerrero, Ana Maria; Talsma, Tiffany; Allen, Brendan; Jarvis, Andy; Golden, Aaron; Spillane, Charles (Frontiers in Climate, 2022)
Systematic tools and approaches for measuring climate change adaptation at multiple scales of spatial resolution are lacking, limiting measurement of progress towards the adaptation goals of the Paris Agreement. To address this, we are developing a ‘Biomass Climate Adaptation Index’ (Biomass CAI) for agricultural systems, where climate adaptation progress across multiple scales can be measured by satellite remote sensing. A Biomass CAI can be used at global, national, landscape and farm-level to remotely monitor agri-biomass productivity associated with adaptation interventions, and to facilitate more tailored ‘precision adaptation’. The proposed Biomass CAI can places focus on decision-support for end-users to ensure that the most effective climate change adaptation investments and interventions can be made in agricultural systems.